Edukasi Penatalaksanaan Dismenorea pada Wanita Usia Subur di PMB Lina Contesa - Lina Contesa; Novi Rida Eriyani (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
Dysmenorrhea is one of the most common reproductive health problems among women of reproductive age and can interfere with daily activities and productivity, while limited knowledge regarding proper management often leads to ineffective handling of menstrual pain. This community service activity aimed to improve the knowledge of women of reproductive age regarding dysmenorrhea management through health education at PMB Lina Contesa. The activity employed a pre-experimental design with a one-group pretest–posttest approach involving women of reproductive age visiting PMB Lina Contesa. Health education was delivered through counseling and interactive discussions using leaflet media. Knowledge levels were measured before and after the intervention using a structured questionnaire and analyzed descriptively and comparatively. The results showed an increase in participants’ knowledge after the educational intervention, with most respondents shifting from low to moderate knowledge levels before education to good knowledge levels after education. These findings indicate that health education on dysmenorrhea management is effective in improving women’s understanding, highlighting the importance of continuous educational programs in midwifery care settings as a promotive and preventive strategy for women’s reproductive health